Contextualizing sustainable development frameworks in oil and gas projects: Cultural adaptation and community prosperity - Ira Setiowati (Kemakmuran Hijau: Jurnal Ekonomi Pembangunan, 2025)
Background: Different local communities around the world whether it is indigenous or communities who has been lived in the area for several generation, have experience economic growth or challenges due to oil and gas facility development. Indonesia, an archipelago with large reserves of oil and natural gas, has become one of the regions experiencing significant development of oil and gas facilities in areas with diverse local cultures. Some communities have success stories, while others left with suffering. Observation indicate that this is due to cultural differences and inherent characteristic of people in different region. Methods: This study will be based on the literature study and writer’s observation in various communities around oil and gas development project in Indonesia. Findings: The numerous issues of inequality caused by development have led investors concerned with equitable community welfare to agree on issuing a sustainable development framework. One aspect often overlooked by developers and investor syndicates is that developers' plans to improve local community welfare frequently use generic templates without considering the specific conditions and situations of the local community. A single development framework cannot be universally applied to all projects. Factors such as culture, lifestyle, the character of the local population, and customary norms play a crucial role in planning an appropriate approach for developing local communities in tandem with project progression. Conclusion: It is anticipated that the findings of this study will assist future oil and gas development project stakeholders and the government of Indonesia in devising and planning a suitable approach to engage with local communities, ensuring their prosperity from the industry without compromising their cultural practices. Novelty/Originality of this article: This research offers originality by emphasizing the contextual adaptation of development frameworks to local cultural settings instead of applying a universal model.